MANAJEMEN PENGELOLAAN BISNIS AIR BERSIH DAN AIR MINUM UNTUK KESEIMBANGAN PENGELOLAAN LINGKUNGAN GUNA KEBERLANGSUNGAN KEHIDUPAN - Lona noviani; H Achmad Rifai (LPPM Universitas Banten jaya, 2021)
The era of modern globalization and the industrial revolution which is rapidly developing, and accompanied by an explosion in the growth of the population which is increasing, which is also followed by the increasingly rapid industrial growth in an effort to meet the needs needed to fulfill human desires. The increasing number of human population and the rapid number of industries on this earth indirectly requires the availability and supply of clean water / drinking water which is adequate and suitable for use. The increasing number of population requires open land that is very wide and spread out for the construction of settlements as a place to live along with the supporting infrastructure needed to meet the needs of activities in accordance with human living standards, and the rapid number of these industries also requires open land which is quite wide and adequate as an area modern industry with all adequate infrastructure to support industrial activities that meet the standards as a modern industrial area. Management of Clean Water and Drinking Water Business Management as an effort to reduce the impact of the use of open land and natural resources in it for the needs of human settlements and business development in newly developing industrial areas which will have an impact on the shrinking of open land as a reservoir for reserve availability of resources underground water and surface water reservoirs to accommodate rainfall for human life. Management efforts are needed in managing the needs of residential settlements and the needs of industrial estates in supporting production operations. Management is very important as an effort to maintain a balance in doing business for profit, but also trying to maintain and try to balance the environment for the continuity of human life. , this can be done jointly by the government, entrepreneurs, and society at large and in a sustainable manner